Concomitants of lower record statistics for Bivariate Pseudo Powered Inverse Rayleigh distribution. - Nayabuddin; Raghav, Yashpal Singh (Brazilian Journal of Biometrics, 2025)
The concept of p- th record value was introduced by Dziubdziela and Kopocinski (1976). In this paper, we have considered concomitants of p- th lower record values (LRV) for Bivariate Pseudo Powered Inverse Rayleigh (BPPIR) distribution. Further single and joint distribution of concomitants of p- th LRV are obtained and expressions for single and product moments are derived. Additionally, we provide the minimum variance linear unbiased estimator of the location and scale parameters of the concomitants of p-th lower record values. The tables for survival function and hazard function has also been obtained. The explicit expression for the reliability is also derived for BPPIR distribution.